Aflatoxin B1 Disrupts Gut-Microbial Metabolisms of Short-Chain Fatty Acids, Long-Chain Fatty Acids, and Bile Acids in Male F344 Rats. (20th April 2018) - Zhou, Jun; Tang, Lili; Wang, Jincheng; Wang, Jia-Sheng
Abstract: In this study, male F344 rats were orally exposed to aflatoxin B1 (AFB1 ) at 0, 5, 25, and 75 μg/kg for 4 weeks. Rat feces were collected from 2 to 4 weeks following exposure and were assessed for gut-microbiota-dependent metabolites. Gut-microbiota-related organic acids were quantitated in the feces using 2-nitrophenylhydrazine derivatization coupled HPLC-profiling method which was validated and showed good reliability, accuracy and sensitivity. After 2-week exposure, AFB1 significantly reduced the levels of fecal short-chain fatty acids (SCFAs) with an over 70% reduction in the high-dose group (75 μg/kg). Mixed-effects model revealed an inverse correlation between AFB1 dose and fecal levels of SCFAs, but no significant time effect was found. When compared with the control, oral exposure to middle-dose AFB1 (25 μg/kg) resulted in remarkable elevations of fecal cholic acid (2.18-fold), linoleic acid (cis-9, cis-12–18:2) (11.3-fold), pentadecanoic acid (15: 0) (3.68-fold), pyruvic acid (4.56-fold), and 3-phenyllactic acid (3.74-fold), but deoxycholic acid level was reduced by 41% in the low-dose group (5 μg/kg). These results demonstrated the disruptions of several important gut-microbiota metabolic pathways, including the synthesis of SCFAs, pyruvic acid related pathways, metabolisms of amino acids, bile acids and long-chain fatty acids, which may further affect host digestive efficiency, energy supply, intestinal immunity, production of neurotransmitters, and enterohepatic cross-talk. Our study suggests that the impairment of gut-microbiota-dependent metabolism may contribute to pathological mechanisms of AFB1 -induced adverse health effects.